A mechanistic study of the electro-oxidation of bromide in acetonitrile and the room temperature ionic liquid, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide at platinum electrodes - Allen, G; Buzzeo, M; Villagran, C; Hardacre, C; Compton, R (2005)
The oxidation of bromide has been investigated by linear sweep and cyclic voltammetry at platinum electrodes in the room temperature ionic liquid, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide, ([C 4mim][NTf 2]), and the conventional aprotic solvent, acetonitrile, (MeCN). Similar voltammetry was observed in both solvents, despite their viscosities differing by more than an order of magnitude. DigiSim ® was employed to simulate the voltammetric response. The mechanism is believed to involve the direct oxidation of bromide to bromine in a heterogeneous step, followed by a homogenous reaction to form the tribromide anion:2Br-→Br2+2e-Br2+Br-→kbkfBr3-KeqAthigher potentials, the tribromide anion dissociates to bromine, Br 2, and bromide, Br -, which is immediately oxidised, leading to the emergence of a second anodic wave. Irreversible electrode kinetics were inferred from Tafel analysis and removal of the first electron is believed to be the rate-determining step in the formation of bromine. The equilibrium constant, K eq, whereKeq=[Br3-][Br2][Br-]was found to be 3 × 10 3 and 9 × 10 6 M -1 in the ionic liquid and in acetonitrile, respectively. An equilibrium constant, K complex for the complexation of 1-ethyl-3-methylimidazolium bromide in acetonitrile was found to be 35.1 M -1. © 2004 Elsevier B.V. All rights reserved.